Perlindungan Hukum Terhadap Wisatawan Menurut Undang-Undang Nomor 10 Tahun 2009 Tentang Kepariwisataan - Firya Oktaviarni (Wajah Hukum, 2018)
Tourism is the country's foreign exchange contributing sector, so tourism is needed. However, there are some cases that occur at tourist attractions such as a tourist being a sinking victim, a tourist dies at a tourist location and a tourist becomes a victim of the price of admission at tourist sites. For this reason, legal protection is needed for tourists so that losses suffered are not always given to tourists. The research objective is to find out the legal protection of tourists according to Law Number 10 of 2009 concerning Tourism. The method used is normative juridical research, legal material in the form of primary and secondary legal materials, research collected with literature study and qualitative normative analysis techniques